Diseño gráfico para el catalogo de la obra artística "Guguchahis y fetiches de fertilidad", del artista Pujilense Joselito Otañez en la modalidad de trabajo de titulación - Bracho Pasquel, Luis Javier Vásconez Albán, Diego Sebastián (2018)
The purpose of this research project was to prepare the catalog of the artistic work "Guguchachis y Fetiches de Fertilidad" by the Pujilense artist Joselito Otáñez, since it is stored and in constant deterioration in the workshop-home of the artist of it. the pieces can return to the current art circuit.Due to this situation it was necessary to make a printed medium such as the catalog or artist's book, in order to reach a new audience. To obtain the information found in the pages of the catalog, texts that are owned by Joselito Otáñez Balseca were used, thus carrying out a textual information survey of the work and the pieces that make up the same, afterwards fieldwork was carried out , arriving at the artist's workshop where the work was photographed in its entirety.In this coexistence with the ceramics, with the texts and with the artist, it was possible to identify the graphic line with which the work was conceived, in this way the graphic concept that was captured in the artist's book or catalog through techniques and tools was obtained. of the editorial design that served to distribute the elements, both graphic and textual, within a visual harmony. With the conception of the catalog it was possible to expand the diffusion range of the work, making use of the project methodology, which allowed the correct execution of the project.